The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/01.sa.0000450929.24556.63
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Evaluating Presurgery Neuroanatomical Biomarkers for Postoperative Cognitive Decline After Total Knee Arthroplasty in Older Adults

Abstract: Background-Total knee arthroplasty improves quality of life but is associated with postoperative cognitive dysfunction in older adults. This prospective longitudinal pilot study with a parallel control group tested the hypotheses that: 1) nondemented adults would exhibit primary memory and executive difficulties after total knee arthroplasty, and 2) reduced preoperative hippocampus/entorhinal volume would predict postoperative memory change, whereas preoperative leukoaraiosis and lacunae volumes would predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
(71 reference statements)
0
11
1
Order By: Relevance
“…Patient recovery could be expedited. The rate of POCD in the HIBIS group of the current study (3.3%) is much lower than the reported rate in patients receiving noncardiac surgical procedures (25%-44%) (Li, Wen, Zhao, Hang, & Mandell, 2013;Moller et al, 1998;Monk & Price, 2011;Price et al, 2014). Such a difference could be attributed to differences of a variety of factors, including the definition of POCD, surgery type, and patient demographic features.…”
Section: Discussioncontrasting
confidence: 74%
“…Patient recovery could be expedited. The rate of POCD in the HIBIS group of the current study (3.3%) is much lower than the reported rate in patients receiving noncardiac surgical procedures (25%-44%) (Li, Wen, Zhao, Hang, & Mandell, 2013;Moller et al, 1998;Monk & Price, 2011;Price et al, 2014). Such a difference could be attributed to differences of a variety of factors, including the definition of POCD, surgery type, and patient demographic features.…”
Section: Discussioncontrasting
confidence: 74%
“…A strength of this study is the Successful Aging after Elective Surgery data, 22 which is remarkable for its longitudinal follow-up of more than 500 surgical patients using well-validated delirium measures and a neuropsychologic test battery sensitive to global and domain-specific cognitive change. 60,61 Others have also reported associations between postoperative delirium and postoperative cognitive dysfunction at hospital discharge or 1 month, but not at later follow-up. 9,57,58 Franck et al 54 only found an association between postoperative delirium and postoperative cognitive dysfunction in a subgroup of participants, and concluded that there was no clear evidence that delirium is independently associated with postoperative cognitive dysfunction beyond 1 week after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting description of functional connectivity changes constituting a normal peri-anesthetic trajectory in healthy older adults will fill a gap in our current understanding and serve as a baseline for comparison with studies employing fMRI to investigate postoperative cognitive function in surgical patients. [19][20][21][22] To this end, we report presently on analysis of rs-fMRI data for 62 healthy adult subjects. Table 1.…”
Section: Introductionmentioning
confidence: 99%